PEMANFAATAN DANA DESA DALAM MENINGKATKAN PEMBANGUNAN DI DESA HUNTU UTARA KECAMATAN BULANGO SELATAN KABUPATEN BONE BOLANGO - Nur Eng Mokodompit; Nazir Padungge (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2022)
This study aims to determine how the utilization and use of village funds in improving development in North Huntu Village, South Bulango District, Bone Bolango Regency. This study uses a qualitative approach and uses interview instruments to selected informants.The results of the study concluded that the use of village funds in supporting development in Huntu Utara Bulango Selatan Village had been carried out effectively in achieving village development. The utilization of village funds can be seen from the three indicators studied, namely objectives, financing structure, and community support. These three indicators have been running effectively, therefore the village of North Huntu in the evaluation of the use of village funds is included in the category of not having findings. Thus, the utilization of village funds has been able to increase development in North Huntu Village, South Bulango District, Bone Bolango Regency.